2020
DOI: 10.25046/aj050296
|View full text |Cite
|
Sign up to set email alerts
|

Legal Regulation as Driver for Sustainable Development of Nigeria’s Solid Mineral Sector

Abstract: The need to optimally explore Nigeria's diverse mineral resource endowments via sustainable value chain practices has, in recent times, been the focus of the Nigerian government and relevant stakeholders. This development has amongst other things, been made a necessity since the decline in Nigeria's crude oil export and earnings, as well as the increased effort and commitment of the government to significantly diversify the economy from reliance on agriculture and the oil and gas sectors. This challenge has di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…This is in line with the statement of Baucus and Near [45] that large enterprises are more likely to be involved in corruption due to the dynamic competitive environment. This research did not focus on whether there are any differences in the behavior patterns of employees of single industries, although previous studies have revealed that there are certain sectors, where the effect of corruption on sustainable development is particularly high, such as the building industry [95], the mining industry [96], the energy industry [97], the fishery [98], health care [99] and education [9].…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the statement of Baucus and Near [45] that large enterprises are more likely to be involved in corruption due to the dynamic competitive environment. This research did not focus on whether there are any differences in the behavior patterns of employees of single industries, although previous studies have revealed that there are certain sectors, where the effect of corruption on sustainable development is particularly high, such as the building industry [95], the mining industry [96], the energy industry [97], the fishery [98], health care [99] and education [9].…”
Section: Discussionmentioning
confidence: 99%